USULAN DESAIN SPRAY AERATOR PADA WASTE WATER TREATMENT PLANT PT INDOFOOD CBP SUKSES MAKMUR, TBK PALEMBANG - meylinda mulyati (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2016)
One of the problems in the waste treatment process of PT Indofood is the aeration proces. The active sludge  is in the aeration basin serves as a medium for living bacteria mesophyll. Activated sludge is often attached to the diffuser. This diffuser serves as a conduit of oxygen to the aeration basin. Because of this, PT Indofood must replace the diffuser 36 annually. The Price of one diffuser is Rp 2.500.000,00, so every year PT Indofood must pay Rp 90,000,000.00 only for diffuser. Based on these facts, we propose to design of  economical spray aerator that  has the same function as a diffuser that exists today as a provider of oxygen to the aeration basin.The design of the proposed spray aerator has a height of 3m pipe with a diameter of 1.5 inch diameter hole in each pipe of 7.5 mm, has 1146 holes with a distance of 2.6 cm each hole and a pressure of 70 kPa capable of minimizing the expenses of Rp 884,885,640.00.Proposed draft spray aerator has a payback period of 31 days to the break even point (BEP) of Rp 13,674,502.00, and the value of average rate of return (ARR) of 94.11%, and the net present value (NPV) of Rp 4,610 .617.872,00, so that the investment project for the installation of spray aerator well done.